A compact and automated ex vivo vessel culture system for the pulsatile pressure conditioning of human saphenous veins. (30th July 2013) - Piola, Marco; Prandi, Francesca; Bono, Nina; Soncini, Monica; Penza, Eleonora; Agrifoglio, Marco; Polvani, Gianluca; Pesce, Maurizio; Fiore, Gianfranco Beniamino
Abstract: Saphenous vein (SV) graft disease represents an unresolved problem in coronary artery bypass grafting (CABG). After CABG, a progressive remodelling of the SV wall occurs, possibly leading to occlusion of the lumen, a process termed 'intima hyperplasia' (IH). The investigation of cellular and molecular aspects of IH progression is a primary end‐point toward the generation of occlusion‐free vessels that may be used as 'life‐long' grafts. While animal transplantation models have clarified some of the remodelling factors, the pathology of human SV is far from being understood. This is also due to the lack of devices able to reproduce the altered mechanical load encountered by the SV after CABG. This article describes the design of a novel ex vivo vein culture system (EVCS) capable of replicating the altered pressure pattern experienced by SV after CABG, and reports the results of a preliminary biomechanical conditioning experimental campaign on SV segments. The EVCS applied a CAGB‐like pressure (80–120 mmHg) or a venous‐like perfusion (3 ml/min, 5 mmHg) conditioning to the SVs, keeping the segments viable in a sterile environment during 7 day culture experiments. After CABG‐like pressure conditioning, SVs exhibited a decay of the wall thickness, an enlargement of the luminal perimeter, a rearrangement of the muscle fibres and partial denudation of the endothelium. Considering these preliminary results, the EVCS is a suitable system to study the mechanical attributes of SV graft disease, and its use, combined with a well‐designed biological protocol, may be of help in elucidating the cellular and molecular mechanisms involved in SV graft disease. Copyright © 2013 John Wiley & Sons, Ltd.